Bible-Based Environmental Conservation for the 21st Century and Application to Present Life Situations - Rugyendo, Medard (Journal of African Interdisciplinary Studies, 2018)
For many, it is unbelievable but the Bible has a great deal to say about the environment and its conservation. Also, environmental crisis is a concern to many in the world today but whenever such challenges come, most people think and believe that it is a science-related, hence the need for a science-based environmental solution. There is general biblical ignorance as far as environmental issues are concerned yet the Bible is an all-round book for guiding Christians in all matters of life. Thus, many of our environmental problems are rooted in the Christian faith as this paper will expose. Therefore, the purpose of this paper is to present the contribution of Scripture towards environmental conservation and expose their implications therein.